2014
DOI: 10.1007/s00125-014-3183-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating natriuretic peptide concentrations reflect changes in insulin sensitivity over time in the Diabetes Prevention Program

Abstract: Aims/hypothesis We aimed to study the relationship between measures of adiposity, insulin sensitivity and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in the Diabetes Prevention Program (DPP). Methods The DPP is a completed clinical trial. Using stored samples from this resource, we measured BMI, waist circumference (WC), an insulin sensitivity index (ISI; [1/HOMA-IR]) and NT-proBNP at baseline and at 2 years of follow-up in participants randomised to placebo (n=692), intensive lifestyle interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The discrepancy in availability of samples was related to prior sample use for other biomarker studies in the DPP as well as discontinuation of the troglitazone arm. [23] Funding: Research reported in this publication was supported by the National Heart, Lung, and Blood Institute grants K12 HL109019, 1K23HL128928-01A1, and R01-HL-086875; the National Center for Advancing Translational Sciences of the National Institutes of Health award numbers UL1TR000445 (Vanderbilt University) and DK099249-01A1 to GAW. During the DPP and DPPOS, the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) of the National Institutes of Health provided funding to the clinical centers and the Coordinating Center for the design and conduct of the study, and collection, management, analysis, and interpretation of the data (U01 DK048489…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy in availability of samples was related to prior sample use for other biomarker studies in the DPP as well as discontinuation of the troglitazone arm. [23] Funding: Research reported in this publication was supported by the National Heart, Lung, and Blood Institute grants K12 HL109019, 1K23HL128928-01A1, and R01-HL-086875; the National Center for Advancing Translational Sciences of the National Institutes of Health award numbers UL1TR000445 (Vanderbilt University) and DK099249-01A1 to GAW. During the DPP and DPPOS, the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) of the National Institutes of Health provided funding to the clinical centers and the Coordinating Center for the design and conduct of the study, and collection, management, analysis, and interpretation of the data (U01 DK048489…”
Section: Study Populationmentioning
confidence: 99%
“…NT-proBNP was measured as previously described. [23] Briefly, venous blood samples were drawn from subjects according to a standardized manual of operations for the Diabetes Prevention Program. Collected blood was immediately processed at each study site with preparation of serum aliquots that were frozen initially at -20˚C, then shipped on dry ice to the Central Biochemistry Laboratory at the University of Washington for long-term storage at -80˚C.…”
Section: Nt-probnp and Covariatesmentioning
confidence: 99%
“…Moreover, genetic polymorphism in natriuretic peptide receptor sequences has also been shown, which might be involved in increased clearance and reduced circulating levels in homozygous C/C carriers [ 12 ]. Interestingly, prospective population-based studies have shown that low natriuretic peptides levels are associated with an increased risk of diabetes incidence [ 12 14 ] and an inverse relationship between natriuretic peptide and insulin sensitivity has also been found [ 15 17 ]. Further, in overweight and obese persons natriuretic peptides levels increase after either lifestyle intervention that reduced weight or bariatric surgery [ 18 22 ], although circulating levels remain lower than in persons with cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In a secondary analysis of data from the Diabetes Prevention Program (DPP), it was recently suggested that NT-proBNP may provide a robust marker of insulin sensitivity in patients with prediabetes. 22 Of note, however, this analysis did not adjust for either renal function or adiponectin. In this regard, the observed attenuation of the independent association of NT-proBNP with Matsuda index upon adjustment for adiponectin in the current study ( Table 3 Model associated with increased serum adiponectin in adults of mean age 64.8 years who did not have CVD at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…In a secondary analysis of data from the Diabetes Prevention Program (DPP), it was recently suggested that NT‐proBNP may provide a robust marker of insulin sensitivity in patients with prediabetes . Of note, however, this analysis did not adjust for either renal function or adiponectin.…”
Section: Discussionmentioning
confidence: 99%